2020
DOI: 10.1002/app.49837
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl alcohol/multi‐walledcarbon nanotubes nanocomposites with ordered macroporous structures prepared byice‐templating

Abstract: We demonstrate in this study that it is possible to prepare three‐dimensionally ordered macroporous polymer structures by ice‐templating. Polyvinyl alcohol (PVA) was used as a model system in this study, but the processing route proposed here can be applied to other polymer systems. Multi‐walled carbon nanotubes (MWCNTs) were incorporated into the PVA matrix at concentrations up to 12 wt% to investigate the influence of this addition on the mechanical and electrical properties of the obtained scaffolds. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…As the dislocation density grows, the dislocations' motion is constrained, thereby increasing strength. For GNP-reinforced composites, researchers [36] revealed that the following formula (2) can be used to define the improvement in strength to yield vs. CTE. A similar procedure is offered for CNTreinforced composites.…”
Section: Mechanical Tests Of Compositesmentioning
confidence: 99%
“…As the dislocation density grows, the dislocations' motion is constrained, thereby increasing strength. For GNP-reinforced composites, researchers [36] revealed that the following formula (2) can be used to define the improvement in strength to yield vs. CTE. A similar procedure is offered for CNTreinforced composites.…”
Section: Mechanical Tests Of Compositesmentioning
confidence: 99%